Предмет: Алгебра,
автор: iliyar2001
помогите представить выражение в виде многочлена
(x-2)(x+3)+(x+2)(x-3)
(a-1)(a+2)+(a+1)(a-2)
(a+1)(a+2)+(a+3)(a+4)
(x-1)(x-2)+(x-3)(x-4)
Ответы
Автор ответа:
0
1. (x-2)(x+3) + (x+2)(x-3) = x² +3x - 2x - 6 + x² - 3x + 2x - 6 = 2x² - 12 = 2(x² - 6)
2. (a-1)(a+2)+(a+1)(a-2) = a² + 2a - a -2 + a² -2a+a-2 = 2a² - 4 = 2(a²-2)
3. (a+1)(a+2)+(a+3)(a+4) = a² + 2a + a +2 + a² + 4a + 3a + 12 = 2a² + 10a + 14 = 2(a² + 5a + 7)
4. (x-1)(x-2)+(x-3)(x-4) = x² -2x - x +2 +x² -4x -3x +12 = 2x² -10x + 14 = 2(x² -5+7)
2. (a-1)(a+2)+(a+1)(a-2) = a² + 2a - a -2 + a² -2a+a-2 = 2a² - 4 = 2(a²-2)
3. (a+1)(a+2)+(a+3)(a+4) = a² + 2a + a +2 + a² + 4a + 3a + 12 = 2a² + 10a + 14 = 2(a² + 5a + 7)
4. (x-1)(x-2)+(x-3)(x-4) = x² -2x - x +2 +x² -4x -3x +12 = 2x² -10x + 14 = 2(x² -5+7)
Похожие вопросы
Предмет: Математика,
автор: nikulinivann
Предмет: Русский язык,
автор: looloolool
Предмет: Английский язык,
автор: sabzirolol99
Предмет: История,
автор: СладунькА
Предмет: Биология,
автор: krekshin